2019
DOI: 10.1089/mdr.2018.0087
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Acinetobacter baumannii Recovered from Swine Manure

Abstract: Recently, concerns have been raised about the possibility of Acinetobacter baumannii transmission between animals and humans. So far, A. baumannii has been reported in animals with which people can come into contact. The presence of this pathogen in animal manure presents an equally important public health risk. In this study, we report the finding of two A. baumannii isolates in swine manure from a Croatian pig farm. Both isolates shared features with the widespread human clinical isolates: affiliation to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
8
2
Order By: Relevance
“…Recently concerns have also been raised about the possibility of transmission of multiresistant A. baumannii between animals and humans. The occurrence of this pathogen in livestock represents a further notable risk of transmission to humans and further into hospitals [32,33]. The capability of A. baumannii to survive harsh conditions, including disinfection, fosters its persistence in hospital environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently concerns have also been raised about the possibility of transmission of multiresistant A. baumannii between animals and humans. The occurrence of this pathogen in livestock represents a further notable risk of transmission to humans and further into hospitals [32,33]. The capability of A. baumannii to survive harsh conditions, including disinfection, fosters its persistence in hospital environments.…”
Section: Discussionmentioning
confidence: 99%
“…ST195, which is dominant in Austria, is also the most frequent ST in Croatia, a country with a lot of students and personal exchange with Austria. Notably, A. baumannii isolates with ST195 have also recently been detected in two isolates in a Croatian pig farm [32], from Austria, as a country with intensive animal husbandry, up to now, no cases have yet been reported. OXA-72 is the dominant CHDL in all geographic regions of Croatia in contrast to Austria in which OXA-58 predominates [42,50].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, similar strains of Enterococcus faecium resistant to vancomycin were detected in pig manure and in clinical samples (Freitas et al., 2011a). Carbapenem‐resistant A. baumannii was also detected in pig manure (Hrenović et al., 2019).…”
Section: Appendix F – Antimicrobial‐resistant Bacteria and Resistance Genes Of High Public Health Relevance In Environmental Sources Of Fmentioning
confidence: 99%
“…Noteworthy is the presence of varied ARGs in manures and in contaminated irrigation water conferring resistance to CIAs, and that are common in clinical human isolates associated with mobile genetic elements, e.g. bla CTX‐M-1 , bla CTX‐M-3 , bla CTX-M‐14 , bla CTX-M‐15 , bla CTX‐M-9 , bla CTX-M‐27 , bla OXA‐23 , bla OXA‐48 , bla NDM‐5 and bla VIM‐1 (Hrenović et al., 2019).…”
Section: Appendix F – Antimicrobial‐resistant Bacteria and Resistance Genes Of High Public Health Relevance In Environmental Sources Of Fmentioning
confidence: 99%
“…Moreover, two most recent studies reported the presence and survival of carbapenem-resistant organisms harboring a plasmid-borne bla OXA-23 gene from swine manure environment from a Croatian pig farm and NDM-5 producing E. coli ST156 from a poultry farm in China. These suggest the possible dissemination of CRE in the food chain through animal manure fertilization [ 111 , 112 ]. On the other hand, irrigation water and various water matrices are also considered as major source of fresh produce contamination with resistant bacteria including CRE that can potentially be transferred to the consumer especially when consumed raw [ 113 ].…”
Section: Carbapenemases-producing Enterobacteriaceae mentioning
confidence: 99%